Research of Vertical via Based on Silicon, Ceramic and Glass - Wenchao Tian; Sixian Wu; Wenhua Li (Micromachines, 2023)
With the increasing demand for high-density integration, low power consumption and high bandwidth, creating more sophisticated interconnection technologies is becoming increasingly crucial. Three-dimensional (3D) integration technology is known as the fourth-generation packaging technology beyond Moore’s Law because of its advantages of low energy consumption, lightweight and high performance. Through-silicon via (TSV) is considered to be at the core of 3D integration because of its excellent electrical performance, lower power consumption, wider bandwidth, higher density, smaller overall size and lighter weight. Therefore, the particular emphasis of this review is the process flow of TSV technology. Among them, the research status of TSV hole etching, deep hole electroplating filling and chemical mechanical planarization (CMP) in TSV preparation process are introduced in detail. There are a multitude of inevitable defects in the process of TSV processing; thus, the stress problems and electrical characteristics that affect the reliability of TSV are summarized in this review. In addition, the process flow and process optimization status of through ceramic via (TCV) and through glass via (TGV) are discussed.